The Tiber between Latins and Etruscans (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2024)
Forty years after the conference “Il Tevere e le altre vie d’acqua del Lazio antico”, in which Giovanni Colonna and I addressed the boundaries of the Latins and the Etruscans, our documentation has significantly expanded with the discovery of Mycenean presence at Vaccina and Casale Nuovo and the new excavations from Rome and its surroundings. The overall picture does not seem to have fundamentally changed: from a substantial homogeneity among the populations north and south of the Tiber up until the late 11th century, clear differences and cultural characteristics of the Etruscans and the Latins emerge thereafter, along with the rise of major centers such as Tarquinia or Rome. Dopo 40 anni dal convegno “Il Tevere e le altre vie d’acqua del Lazio antico”, in cui con Giovanni Colonna affrontammo i confini dei Latini e degli Etruschi la nostra documentazione si è notevolmente arricchita con le scoperte a Vaccina e Casale Nuovo della presenza micenea e i nuovi scavi da Roma e dintorni. Il quadro non sembra sostanzialmente cambiato: da una sostanziale omogeneità delle popolazioni a nord e a sud del Tevere a partire dallo scorcio dell’XI secolo emergono nette le differenze e le caratteristiche culturali degli Etruschi e i dei Latini e la nascita dei grandi centri come Tarquinia o Roma.
Keywords: Tiber; Etruscans; Latins; Tyrrhenian Sea; populi Albenses